Risk factors of neonatal hypoglycemia in Banda Aceh: A Retrospective Cross-Sectional Study - Aidil Fittriani Ayu; Darnifayanti Darnifayanti; Mulya Safri; Sulaiman Yusuf; Syafruddin Haris; T. M. Thaib (AcTion: Aceh Nutrition Journal, 2026)
Hypoglycemia is the most common metabolic disorder in newborns during the first two days of life, with a global prevalence of 5-15% in at-risk populations. This condition can cause permanent neurological damage and intellectual disabilities. Objective: To analyze the risk factors of neonatal hypoglycemia at Dr. Zainoel Abidin Hospital, Banda Aceh. Methods: This retrospective cross-sectional study used medical records from January to December 2024. The key predictors included gestational age, birth weight, maternal diabetes mellitus, eclampsia, and delivery mode. All eligible records (n=448) were included. Data were analyzed using SPSS version 29 with the chi-square test and multiple logistic regression. Hypoglycemia (blood glucose <45 mg/dL within 24 h of birth) was found in 67 (15.0%) infants. Multivariate analysis identified cesarean section as the strongest independent predictor (AOR=3.850; p<0.001), followed by birth weight <2500 g (AOR=6.345; p=0.004), and prematurity <37 weeks (AOR=3.383; p=0.001). In conclusion, cesarean delivery, prematurity, and low birth weight were independent risk factors for neonatal hypoglycemia after multivariate adjustment.